Implementation of Four Land Order in the Field of Absentee Ownership of Land Rights - Pradana, Yuda Sony Adhi; Darmadi, Nanang Sri (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2023)
This research aims to find out, explain and discover the obstacles to the implementation of Four Land Order in the field of absentee land ownership. The approach method in this research is a sociological juridical approach. The research specification is the implementation of the Four Land Order in the field of absentee land ownership. The data required includes primary data on the implementation of Four Land Order in the field of absentee land ownership. Data was taken using interviews, observation and literature study methods. The data analysis method uses interactive techniques. Interactive analysis means data is analyzed through three stages, namely reducing data, presenting data and drawing conclusions. Based on the research, it was concluded that the implementation of Four Land Order in the field of absentee land ownership in Kudus Regency is still less than optimal. Many land sales and purchases are carried out under the hands of the Land Administration Order. Ultimately, the goal of land reform to improve the welfare of farmers in particular, and create a just and prosperous society based on Pancasila in general, has not been able to meet the expectations to be achieved. The obstacles that arise in the implementation of the Four Land Order in the field of absentee land ownership can be grouped into 2 (two) groups, namely internal obstacles and external obstacles.